HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP CARINGPERAWAT PADA RUANG RAWAT INAP DI RUMAH SAKIT MEDISTRA JAKARTA - Siti Fatimah; Nani Marni (Jurnal Afiat : Kesehatan dan Anak, 2021)
Caring where nurses work to further increase their care for their clients. Purposeresearch is to find out whether there is a relationship between knowledge and attitudes of nurses in the inpatient room of Medistra Hospital, Jakarta. Research Methodsdescriptive research method, the number of population is 55 people. Samples were taken using the Rurposive Sanmpling technique as many as 30 respondents. The analysis used univariate and bivariate using chi-square with α =0,5. Result showed a relationship between knowledge and caring attitudes of nurses in the inpatient room of the Medistra Jakarta hospital (p value 0.032).. Conclusion this research shows there is a relationship between knowledge and nurse caring attitudes. in the inpatient room at the Medistra hospital. Suggestion for this study are expected to provide information about the goodness of knowledge with caring attitudes to nurses.